19F NMR Study of the Bilayer Iron-Based Superconductor KCa2Fe4As4F2**Supported by the National Key Research and Development Program of China under Grant No 2017YFA0302901, the National Basic Research Program of China under Grant No 2015CB921304, the National Science Foundation of China under Grant Nos 11674375 and 11634015, and the Strategic Priority Research Program and Key Research Program of Frontier Sciences of the Chinese Academy of Sciences under Grant No XDB07020200. (December 2019) - Shao 邵, Yu-Ting 钰婷; Hong 洪, Wen-Shan 文山; Li 李, Shi-Liang 世亮; Li 李, Zheng 政; Luo 雒, Jian-Lin 建林
Abstract : We report a 19 F nuclear magnetic resonance (NMR) study on single-crystal KCa2 Fe4 As4 F2 ( T c ∼ 33.3 K). The 19 F NMR spectral shape of KCa2 Fe4 As4 F2 is weakly dependent on temperature and the Knight shift is small, which implies weak coupling between the CaF layer and the FeAs layer. The temperature dependence of 1/ 19 T 1 shows a hump below T c, however the 1/ 75 T 1 decreases just below T c, which implies that there are strong in-plane magnetic fluctuations in the CaF layers than in the FeAs layers. This may be caused by the motion of vortices. The absence of the coherence peak suggests unconventional superconductivity in KCa2 Fe4 As4 F2 .